Condition assessment of lower roadway layers for pavement management systems - Pożarycki, Andrzej (Journal of Civil Engineering and Management, 2016)
The process of selecting road maintenance technologies for the Pavement Management System (PMS) can use road pavement moduli of deformation as the substantiating information. Assessment criteria based on either pavement or base course moduli of deformation have strong empirical underpinning, since the stiff plate bearing testing (SPBT) is commonly used worldwide. This paper discusses potential practical applications of plate bearing test numerical simulation based on Falling Weight Deflectometer (FWD) deflection data, and theoretical model based on flexible pavement. It was proven that including a pavement model with stress dependency, the simulated second load-displacement curves meet reliably plate bearing in-situ test conditions for different layers of either subgrade or base courses of road pavement. This methodology is feasible by classifying technical condition of each lower layer of road pavement against requirements towards new pavements. First published online: 19 Nov 2015